2019
DOI: 10.1177/1120700019835641
|View full text |Cite
|
Sign up to set email alerts
|

Trochanteric spurs and surface irregularities on plain radiography are not predictive of greater trochanteric pain syndrome

Abstract: Purpose: Surface irregularities of the greater trochanter have been described as a potential radiographic sign of greater trochanteric pain syndrome (GTPS). We report a diagnostic accuracy study to evaluate the clinical usefulness of trochanteric surface irregularities on plain radiographs in the diagnosis of GTPS. Methods: We retrospectively identified the anteroposterior pelvic radiographs of a consecutive group of 38 patients (representing a 27.5% series prevalence) diagnosed with GTPS (mean age 69.5 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“… 33 However, a recent study found that radiographic surface irregularities are not reliable indicators for clinically diagnosed GTPS, with enthesophytes measuring greater than 2 mm on plain radiographs demonstrating a sensitivity of only 64% and a specificity of 26%. 34 Plain radiographs are primarily useful for the diagnosis of alternative sources of hip pain, including osteoarthritis, avascular necrosis, femoroacetabular impingement, and lumbar spondylosis.…”
Section: Imagingmentioning
confidence: 99%
“… 33 However, a recent study found that radiographic surface irregularities are not reliable indicators for clinically diagnosed GTPS, with enthesophytes measuring greater than 2 mm on plain radiographs demonstrating a sensitivity of only 64% and a specificity of 26%. 34 Plain radiographs are primarily useful for the diagnosis of alternative sources of hip pain, including osteoarthritis, avascular necrosis, femoroacetabular impingement, and lumbar spondylosis.…”
Section: Imagingmentioning
confidence: 99%
“…Barrett et al mention a series prevalence of 27.5%. In addition MRI analysis show peritrochanteric lesion in over 30% [4][5][6] . Following total hip arthroplasty (THA) 4-17% of patients report these symptoms according to previous studies [7][8][9][10][11] .…”
mentioning
confidence: 93%
“…33 Last, the study by Barrett et al included only 38 patients with GTPS, while the present study constitutes the largest series to date on patients with GTPS, with 713 hips included. In contrast to Barrett et al, 1 Hartigan et al 16 reported that proximally directed enthesophytes are a significant predictor for an abductor tendon tear, with an OR of 20.7. This is significantly higher than the value reported in the current study; however, the reference groups are different in the 2 studies.…”
Section: Discussionmentioning
confidence: 82%
“…Subsequent studies have evaluated the association of pertrochanteric calcifications with GTPS with conflicting results. 1,16,29,32 However, to date, no studies have systematically described pertrochanteric calcifications in a large series of patients presenting with GTPS. Furthermore, no studies have evaluated the association between various types of pertrochanteric calcifications and surgically assessed tendon injuries.…”
mentioning
confidence: 99%